2020
DOI: 10.1117/1.ap.2.3.036003
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of vector vortex beams in dispersive media

Abstract: Scattering phenomena affect light propagation through any kind of medium from free space to biological tissues. Finding appropriate strategies to increase the robustness to scattering is the common requirement in developing both communication protocols and imaging systems. Recently, structured light has attracted attention due to its seeming scattering resistance in terms of transmissivity and spatial behavior. Moreover, correlation between optical polarization and orbital angular momentum (OAM), which charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…New methods for creating OAM beams have been explored and their propagation through diffuse media has been studied. Recent works have focused on the beam structure for different orders of OAM after passing through diffuse media 7 , 8 , 13 . As a beam passes through diffuse media, the light is scattered the polarization becomes random and the beam's power decreases 14 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…New methods for creating OAM beams have been explored and their propagation through diffuse media has been studied. Recent works have focused on the beam structure for different orders of OAM after passing through diffuse media 7 , 8 , 13 . As a beam passes through diffuse media, the light is scattered the polarization becomes random and the beam's power decreases 14 .…”
Section: Introductionmentioning
confidence: 99%
“…New methods for creating OAM beams have been explored and their propagation through diffuse media has been studied. Recent works have focused on the beam structure for different orders of OAM after passing through diffuse media 7,8,13 . As a beam passes through diffuse media, the light is scattered the polarization becomes random and the beam's power decreases 14 .Studies of OAM propagation have treated transmission through multi scattering media for communication purposes, including transmission through atmosphere, desert environment and underwater 6,12,[15][16][17][18] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10(a), photons have various physical degrees of freedom, including time, amplitude, polarization, spatial structure, and frequency/wavelength, which are widely adopted in optical communications as information carriers. 117,118 The multiplexing techniques of each dimension lead to wavelengthdivision multiplexing, time-division multiplexing, quadrature amplitude modulation, polarization-division multiplexing, modedivision multiplexing, etc. 119 The AM multiplexing modulation considerably enhances the capacity of optical communications because of the added degree of freedom given by the photonic AM.…”
Section: Optical Information Transmission and Processingmentioning
confidence: 99%
“…The LG modes are the easiest type of vortex beams to generate in a laboratory setting, and excellent reviews exist on the theoretical explanation of OAM, generation of LG beams, and applications using LG beams [36,37]. An extensive study of the vortex beams has found ample applications in the field of communications and optical imaging, among others [35,[38][39][40][41][42][43][44][45][46]. Compared to the traditional Gaussian beam, the use of vortex beams in an imaging system shows significant improvement in the image quality.…”
Section: Orbital Angular Momentum Of Light and Imaging Using Vortex Bmentioning
confidence: 99%